Student Engagement and Motivation in Post-Pandemic Higher Education Mathematics: A Concept Paper (Global Journal of Human-Social Science, 2023)
During the past three years mathematics educators have had to adjust to the online education system and develop new approaches strategies and practices to keep students engaged and motivated Student engagement and motivation have been established in existing research as vital aspects of education To promote engagement and motivation during the pandemic mathematics educators have focused on positive working relationships with students highlighting values such as care and empathy Mathematics educators have also adopted various technological tools to enhance student engagement and motivation As institutions have begun to reintroduce face-to-face classes in the post-pandemic era there is a need to re-examine these approaches and how they may be sustained or improved A significant gap that has remained unexplored in the literature is how mathematics educators maintain or enhance student engagement and motivation upon transitioning to face-to-face or hybrid classes in the post- pandemic era This concept paper is centered on this research gap with recommendations for theory and practice based on current knowledge regarding higher education students motivation and engagement in mathematics
Keywords: mathematics education; student engagement; student motivation; engagement theory; post-pandemic